Utility of immunocytochemistry in diagnosing leptomeningeal metastases from an intrahepatic cholangiocarcinoma. Issue 1 (22nd January 2013) - Chaudhary, Shweta; Klein, Melissa; Mehrotra, Bhoomi; Morgenstern, Nora J.
<x xml:space="preserve">Abstract</x> Isolated spinal leptomeningeal metastases (LMM) without brain metastases are infrequent, accounting for about 1% of all solid tumors. In LMM, cerebrospinal fluid (CSF) analyses are mostly abnormal. Demonstrations of intrathecal tumor markers are highly suggestive, but only a positive cytology is diagnostic. The initial CSF cytology can give a false negative result in up to 40–50% of patients with pathologically proven LMM on autopsy. We report a case of intrahepatic cholangiocarcinoma with spinal LMM confirmed using cytokeratin7 and pancytokeratin (AE1/AE3) immunocytochemical studies on paucicellular cerebrospinal fluid cytospin preparation. Given the paucicellularity of the smears and difficult morphologic categorization, immunocytochemistry is vital for confirmatory diagnosis and can help reduce false negative results. To the best of our knowledgethis is the first case report of cytologically confirmed LMM from an intrahepatic cholangiocarcinoma while the patient was undergoing treatment. Diagn. Cytopathol. 2014;42:54–57. © 2013 Wiley Periodicals, Inc.